Shaping Globalization: London S Merchant Bankers in the Early Nineteenth Century - Llorca-Jana, M (CAMBRIDGE UNIV PRESS, 2014)
This article argues that entrepreneurs, not governments or markets, shaped globalization during the early nineteenth century. The article concentrates on the trading and financial activities of London merchant bankers, and in particular on the different diversification strategies they followed. Although most London merchant bankers remained cautious and did not diversify their operations either geographically or in the products they traded during this period, Huth & Co. established an impressive global network of trade and lending, dealing with over six thousand correspondents worldwide in a wide range of products. This firm shaped globalization well before the transport and communication revolution of the last quarter of the nineteenth century.